Production and Utilisation of Bamboos and related Species in the South Asian Region in the Rural Sector - Sharma, Y. M. L. (Indian Forester, 1988)
Tbe bamboos are used from cradle to the coffin and also in myriad ways in the rural sector of tbe Asian Pacific region. The most commonly used bamboo species in the different countries in the rural sector, and their management, harvesting, regulating, supplies, usages, calorific value, protection against damage and suggestions for developing the bamboo resources bave been presented in this paper .